The Influence of Social Anxiety on Problematic Internet Use (PIU) Among University Students in Makassar - Milenia, Nova Alsa Sabila; Fakhri, Nur Fitriany; Sulastri, Tri (Polteknik Ilmu Pemasyarakatan, 2025)
The development of technology has led to the increasing use of the internet in daily life. However, behind its benefits, excessive internet use can trigger problematic behavior known as problematic internet use (PIU). PIU is characterized by difficulty controlling internet use to the point that interferes with social, academic and psychological functioning. One factor suspected to contribute to PIU is social anxiety. This study aims to exemine the influence of social anxiety on problematic internet use among students in Makassar. This research employed a quantitative method with 308 students. The sampling technique used was accidental sampling. The results showed that social anxiety significantly influences problematic internet use among university students in Makassar, with a significance value of 0.000 (p < 0.05). The R square value was 0,358, indicating that the contribution of social anxiety to problematic internet use among students in Makassar is 35.8%, with a positive influence direction, illustrating that the higher the social anxiety, the higher the problematic internet use. These findings contribute to the development of theories on the effect of social anxiety on problematic internet use and encourage students to be more aware of the importance of managing social anxiety to avoid maladaptive internet use.